Odpowiedź :
a) x²+12x+36 = x²-4x+4
16x=-32
x=-2
b) 4x²-8x = 4x²+16x+16
-24x=16
x= -⅔
c) 2x²-x=2(x²+4x+4)
2x²-x=2x²+8x+8
-9x=8
x=-8/9
16x=-32
x=-2
b) 4x²-8x = 4x²+16x+16
-24x=16
x= -⅔
c) 2x²-x=2(x²+4x+4)
2x²-x=2x²+8x+8
-9x=8
x=-8/9
x²+12x+36=x²-4x+4
12x-4x=4-36
8x=-32|/8
x=4
4x²-8x=4x²+16x+16
-8x-16x=16
-24x=16|/(-24)
x=-24/16=-1,5
2x²-x=2(x²+4x+4)
2x²-x=2x²+8x+8
-x-8x=8
-9x=8|/(-9)
x=-8/9
12x-4x=4-36
8x=-32|/8
x=4
4x²-8x=4x²+16x+16
-8x-16x=16
-24x=16|/(-24)
x=-24/16=-1,5
2x²-x=2(x²+4x+4)
2x²-x=2x²+8x+8
-x-8x=8
-9x=8|/(-9)
x=-8/9